An Analysis of Differences in Online and Offline Learning at Mahardika Elementary School of Denpasar - Sukrawati, Ni Ketut; Rismadewi, Ni Wayan Monik (International Journal of Multidisciplinary Sciences, 2023)
The Covid-19 pandemic impacts the learning process, which was initially carried out face to face turning to online learning (in the network). The pandemic was descending, causing learning to be diverted again into offline learning (outside the network). Thus, this study aims to analyze the difference between online and offline learning in student achievement at Mahardika Elementary School Denpasar. The method used is a qualitative method. Data collection using observation methods, interviews, literature studies and documentation studies. The data that has been collected is analyzed by data collection methods, data reduction, data presentation, conclusion and verification. The results showed that the learning process provided two sides of a coin: online and offline. The teacher used Whatsapp Group Class and Zoom in online activity to deliver the learning material. Whereas in offline learning, learning steps are carried out by preparing learning material by the teacher, discussing material directly in the classroom and conducting a discussion session with students. The teacher can better observe students' development because the exercises given directly will be done independently so that the teacher knows the students' understanding precisely. Difficulties in online and offline learning are both derived from two factors: internal factors and external factors. Difficulties derived from internal factors in online and offline learning are intelligence or intellectual, laziness and health factors. Difficulties derived from external factors in online learning: facilities, internet networks and family environments. In comparison, the difficulties derived from external factors in offline learning are the school environment, school facilities and the ability of teachers to deliver materials to students.